Handbook of Vegetable Science and Technology : (Marcel Dekker, 1998)
This handbook discusses morphology, anatomy, toxonomy,and cultivars...details soil and climatic requirements, propagation, cultural practices, harvesting, and pest and disease control...explains postharvest handling...describes the chemical constituents of each vegetable...